A technique to measure fuel oil viscosity in a fuel power plant. (January 2016) - Delgadillo, Miguel Angel; Ibargüengoytia, Pablo H.; García, Uriel A.
Abstract: The viscosity measurement and control of fuel oil in power plants is very important for a proper combustion. However, the conventional viscometers are only reliable for a short period of time. This paper proposes an on-line analytic viscosity evaluation based on energy balance applied to a piece of tube entering the fuel oil main heater and a new control strategy for temperature control. This analytic evaluation utilizes a set of temperature versus viscosity graphs were defined during years of analysis of fuel oil in Mexican power plants. Also the temperature set-point for the fuel oil main heater output is obtained by interpolating in the corresponding graph. Validation tests of the proposed analytic equations were carried out in the Tuxpan power plant in Veracruz, Mexico. Abstract : Highlights: We tackle a real problem in the fossil fuel power plants combustion control. We utilize analytic equations relating measured variables in the combustion control of a fossil fuel power plant. We describe the experiments conducted and the results obtained. We validated the model using real data from the power plant. We installed a prototype of the viscosity evaluation module in the power plant and we are developing the in situ tests.